Automated breast ultrasound: a novel approach to screening women with dense breasts. (April 2013) - Lenihan, Megan J; Brem, Rachel F
Automated breast ultrasound is likely to be a key player in the future of imaging for women with dense breast tissue. There has previously been a gap in the ability of technology to screen dense breast tissue. Dense tissue can not only obscure cancer when imaged with x-ray mammography, but is also a risk factor, increasing the risk of breast cancer four- to six-fold for women with fibroglandular tissue greater than 60%. Ultrasound has been proven to find cancers that are not visible with mammography. Automated breast ultrasound standardizes the use of ultrasound, producing a more comprehensive and consistent image, which physicians can review quickly and easily. There is a promising future for the use of automated ultrasound for screening women with dense breast tissue. Automated breast ultrasound is proving to be a useful adjunct to mammography, which helps to catch cancer at an earlier and more treatable stage.